Estudo do efeito de diferentes granulometrias no comportamento mecânico de misturas asfálticas densas descontínuas tipo Stone Matrix Asphalt (SMA) - Oliveira Filho, Clonilo Moreira Sindeaux de (2007)
In Brazilian roadways, which concentrate 96.2% of the passengers and 61.8% of the cargo, it is clear the deterioration of asphalt pavements caused by an increasing volume and weight of the vehicle loadings. This configuration strongly contributes to pavement distresses, specially rutting and fatigue cracking. On another hand, the State of Ceará shows a lack of paved roadways, with only 16.0% of paved roads. The Stone Matrix Asphalt (SMA) mixture appeared a few years ago as a solution for minimizing distresses on roadways with high traffic levels. Some researches, however, demonstrate that SMA mixtures with small Nominal Maximum Aggregate Sizes (NMAS) offer similar performances to SMA mixtures with usual NMAS. The objective of the present research was to design SMA mixtures with different gradations in order to study some characteristics of this type of mixture, investigating the effect (i) of the NMAS, (ii) of the percentage of aggregate passing in sieve N. 4 (4.75mm) for 12.5mm NMAS SMA mixtures and (iii) of the compaction type (Marshall × Superpave) on the mechanical behavior of the mixtures. The mixtures were evaluated by (i) resilient modulus, (ii) indirect tensile strength, (iii) fatigue life (stress controlled), (iv) resistance to moisture damage and (v) Cantabro abrasion. The results support the idea that SMA mixtures with small NMAS behave similar to those with usual NMAS. Furthermore, the 4.75mm NMAS SMA appears to be a potential solution for roadways in Ceará, considering the traffic configuration of this state.